Digital Banking Transformation: Opportunities, Challenges, and Collaboration - Widiana Indah Permata; Heru Subiyantoro (Greenation Research & Yayasan Global Resarch National, 2025)
The Covid-19 pandemic has become a cause for concern not only in Indonesia but also in various other countries. The Covid-19 pandemic has been the root cause of significant changes in various aspects, especially in the digital field, and has triggered the acceleration of digital banking transformation from a physical economy to a virtual economy. Digital banking transformation in Indonesia presents various opportunities and challenges and supports the creation of collaboration. This study aims to analyze the opportunities, challenges, and collaborations in the digital banking transformation. The research was conducted using a qualitative approach with a focus on literature review and the collection of the latest news and digital banking practices as supporting data. The results of the study show that digital banking transformation opens up great opportunities for banks to improve effectiveness, efficiency, and productivity as well as innovative services by looking at digital opportunities, digital behavior, and digital transactions that are growing. In addition to creating opportunities, digital banking transformation certainly has challenges such as data leaks, strategic risks that can lead to cost waste, rampant cyber attacks, lack of organizational readiness in terms of human resources, data leak risks that still occur, misuse of technology such as AI for malicious purposes, weak supervision of third parties or outsourcing, uneven communication network infrastructure between regions, and a regulatory framework that is still slow to be adapted by industry players. In addition to opportunities and challenges, digital banking transformation supports collaboration between banks and non-bank financial institutions, fintech, and bigtech to create better, more inclusive, and more efficient financial services. The conclusion of this study is that digital banking transformation requires the right strategy, good risk management, and support for collaboration.